Leadership mentoring and succession in the Charismatic churches in Bushbuckridge : a critical assessment in the light of 2 Timothy 2 :1 - 3 - Mahlangu, Elijah (University of Pretoria, 2014)
Thesis (PhD)--University of Pretoria, 2013.